Numerical issues on brittle shear failure of pier-wall continuous vertical joints in URM dutch buildings. (1st May 2022) - Fusco, Daniela; Messali, Francesco; Rots, Jan G.; Addessi, Daniela; Pampanin, Stefano
Highlights: Nonlinear constitutive laws for simulating glued connections shear failure. Numerical applications on two-storey masonry assemblages under seismic load. Sensitivity study of mechanical parameters of the vertical glued connection. Adoption of smeared crack models for the nonlinear behaviour of masonry. Investigation of numerical issues caused by the brittle failure of the connection. Abstract: Terraced houses built in the Netherland after 1980 are often characterized by the use of large units connected at corners by continuous thin layer mortar joints. Unlike the running bond pattern, usually modelled as a rigid connection, the vertical continuous connection may fail in shear and influence the global seismic capacity of the entire building. This work aims at investigating and comparing different numerical modelling approaches for simulating the vertical connections. Two different constitutive models are adopted to simulate the quasi-brittle nonlinear behaviour of the continuous joint, and their advantages and limitations are pointed out in terms of robustness and accuracy. The study considers both the component level in terms of U-shaped pier-wall configuration, and the full-scale structural level in terms of the global capacity for a two-storey masonry house assemblage, characterized by a running bond arrangement. The results of this work show that the shear failure involving the continuous joint usually reduces the strength capacity of the structure. Both the selection of constitutive models for the connection interface and masonry material are demonstrated to affect the results significantly. Decoupled direct traction-displacement relations for the interfaces appear to provide more robust results than coupled plasticity-based Coulomb friction laws. The selection of either a pre-fixed orthotropic smeared crack model for the masonry or a standard isotropic concrete-like rotating smeared crack formulation is demonstrated to strongly influence the activation of the different failure mechanisms and hence the response of the structure.